Adaptation Atlas Notebook: Analyze women's exposure to climate hazards / Analyser l'exposition des femmes aux aléas climatiques - Youngberg, Brayden; Steward, Peter; Vyas, Shalika; Muller, Lolita; Rosenstock, Todd (2025)
This notebook examines how climate hazards intersect with gender by analyzing women’s exposure to heat, drought, and flooding across Africa. It overlays climate risk data with spatial distributions of the female population to show where women are most affected and how exposure varies by region. Users can explore country-specific patterns and compare hazard intensities to identify areas where climate impacts may deepen existing gender inequalities. By linking climate risks with demographic vulnerability, the notebook supports gender-responsive adaptation planning and highlights where targeted interventions for women are most urgently needed.